Strong and Δ convergence theorems for multivalued mappings in cat(o) spaces - B. Panyanak (2018)
We show strong and Δ convergence for Mann iteration of a multivalued nonexpansive mapping whose domain is a nonempty closed convex subset of a CAT(0) space. The results we obtain are analogs of Banach space results by Song and Wang [2009, 2008]. Strong convergence of Ishikawa iteration are also included. Copyright © 2009 W. Laowang and B. Panyanak.